Pengaturan Obyek Pajak Restoran Di Daerah Berdasarkan Undang-Undang Nomor 1 Tahun 2022 tentang Hubungan Keuangan Antara Pemerintah Pusat dan Daerah - Febry Loupatty; Salmon Eliazer Marthen Nirahua; Heillen Martha Yosephine Tita (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Until now there are no regional regulations regarding restaurant tax objects as a derivative of the implementing regulations of Law Number 1 of 2022. This has created a legal vacuum in the regions and there is no legal certainty for the public, especially taxpayers. The aim of the research is to find out and analyze the regulation of restaurant tax objects and their legal consequences in the regions based on Law Number 1 of 2022 concerning Financial Relations between the Central and Regional Governments. The research methods used are a statutory approach and a conceptual approach. The results of this research show that the regulation of restaurant tax objects based on Law Number 1 of 2022 has undergone regulatory changes which have been integrated into certain goods and services tax objects but have not been regulated in regional regulations. Regulation of restaurant tax objects in the regions can give rise to legal consequences, namely a legal vacuum so that regional tax collection still uses the old regional tax regulations, and the old regional regulations are declared null and void because they are juridically, materially flawed, namely contrary to the public interest/law higher.